"Brainwashing" : Diffusion of a Questionable Concept in Legal Systems. (5th May 2015) - Reichert, Jenny; Richardson, James; Thomas, Rebecca
Abstract : The idea that an individual could be manipulated into performing acts "against their will" created a fear of "brainwashing" and, specifically, new religious movements (NRMs). Courts in the United States initially accepted evidence concerning "brainwashing" in cases involving NRMs, and subsequently the term has been applied in situations involving other behaviors labeled as deviant both in the U.S. and other societies. This has generated challenges for legal systems despite the inability of brainwashing-based claims to meet requirements for admissibility as scientific evidence. Brainwashingbased claims have diffused into other areas of the American legal system, including, for example, custody cases involving allegations of Parental Alienation Syndrome (PAS) as well as in cases involving terrorism. This report presents data on how brainwashing has been treated historically in American legal cases and its current uses within that justice system.